2018
DOI: 10.1038/s41467-018-07630-y
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy silencing by XIST normalizes Down syndrome cell pathogenesis demonstrated for hematopoietic defects in vitro

Abstract: We previously demonstrated that an integrated XIST transgene can broadly repress one chromosome 21 in Down syndrome (DS) pluripotent cells. Here we address whether trisomy-silencing can normalize cell function and development sufficiently to correct cell pathogenesis, tested in an in vitro model of human fetal hematopoiesis, for which DS cellular phenotypes are best known. XIST induction in four transgenic clones reproducibly corrected over-production of megakaryocytes and erythrocytes, key to DS myeloprolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 54 publications
8
46
0
Order By: Relevance
“…Through the establishment of DS-derived induced pluripotent stem cells (iPSCs), independent studies have shown that trisomy 21 alone significantly accelerates the early stages of hematopoiesis [82][83][84][85]. Regardless of whether primitive (yolk-sac type) or definitive (fetal liver type) hematopoiesis was induced, all groups reported an increase in the clonogenic potential of erythroid progenitors and enhanced erythroid differentiation.…”
Section: Insights From Human Ds-induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Through the establishment of DS-derived induced pluripotent stem cells (iPSCs), independent studies have shown that trisomy 21 alone significantly accelerates the early stages of hematopoiesis [82][83][84][85]. Regardless of whether primitive (yolk-sac type) or definitive (fetal liver type) hematopoiesis was induced, all groups reported an increase in the clonogenic potential of erythroid progenitors and enhanced erythroid differentiation.…”
Section: Insights From Human Ds-induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Tet-regulated XIST was stably expressed after Dox treatment in both iPSCs and differentiated cells in previous studies 19,20,21 . Nevertheless, XIST RNA was not detected in our differentiated XIST-Tri21 NPCs, likely due to silencing of the rtTA inserted in the AAVS1 locus.…”
Section: Discussionmentioning
confidence: 95%
“…In one such cell line, XIST was inserted into a copy of chromosome 21 in trisomy 21 iPSCs (Tri21 iPSCs), and a long noncoding RNA induced a series of chromatin modi cations that stably silenced gene transcription across the whole chromosome in cis. Chromosome silencing occurred even in differentiated cells, and various pathologies observed in DS (including proliferative defects, impaired neural differentiation, and haematopoietic abnormalities) were successfully reversed by the transcriptional inactivation of the supernumerary chromosome 20,21 . Using this genome-silencing technology, where XIST RNA expression is regulated by the tetracycline-inducible system, enables researchers to investigate the correlation between gene-expression changes and cellular phenotypes in DS, without limitations caused by transcriptional heterogeneity and differences among cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we have provided an overview of the deletion or silencing of an extra chromosome copy using genome editing technology, cell-autonomous correction of ring chromosomes, and TCLs during the reprogramming process in constitutional aneuploidy disorders. However, most of these approaches still have low efficacy [94,105].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that trisomy 21 upregulates insulin-like growth factor (IGF) signaling to enhance the GATA1 expression aberrantly, thereby causing leukemia in DS. The XIST-mediated trisomy 21 silencing in DS patient-derived iPSCs restored the proper hematopoietic differentiation in vitro [94]. For clinical applications of this method, further improvements are required for the complete silencing of targeted chromosome 21.…”
Section: Conventional Gene-targeting Mediated Dual Drug Selection Casmentioning
confidence: 99%